Selection at Three Levels of Organization: Does Structure Matter? - Sandaker, Ingunn; Couto, Kalliu Carvalho; de Carvalho, Lucas Couto (Behavior & Social Issues, 2019)
The structure, function, and processes of a system modulate human behavior on at least 3 levels of selection: biological, behavioral, and cultural. During phylogenesis, an acquired biological structure will enable the organism to discriminate antecedent and consequent stimuli that are functionally related to response classes. Although the reinforcing value of most stimuli is based on natural selection, the stimuli's control over behavior is mediated by a verbal community. Thus, the reinforcing value of a stimulus is established (a) during phylogenesis when it has adaptive value for that species, (b) during ontogenesis when it has adaptive value for the organism, and (c) culturally when it has adaptive value for a group. If a gene sequence/phenotype, response class, or set of contingencies matches the environment over time (i.e., function), then a structure will become recurrent. Structures are networks of relations that carry information about the adaptive history of a certain system. This paper discusses the ways in which a selectionist explanation of human behavior may incorporate the interdependence of processes, function, and structure at 3 levels of complexity. The cultural behavioral perspective represented by the concept of metacontingency will have its parallel to processes (interlocking behavioral contingencies IBC), function (aggregated product AP), context (receiving system RS), and a recurrent structure (nested interlocking behavioral contingencies n-IBC).